International Migration: A Very Short Introduction - Khalid Koser (New York Oxford University Press, 2016)
"In this Very Short Introduction, Khalid Koser shows why migration matters, and examines its fundamental links with globalization, development, poverty, and human rights. Presenting the human side of topics such as asylum, human trafficking, and cultural integration, he debunks many of the myths surrounding international migration, and reveals how beneficial it can be to economies both at home and abroad."
Includes Index and Illustrations.
Keywords: Immigrants